59 Injuries are preventable, but do Australians think so?. (20th November 2022) - Sweeney, Roisin; Meade, Rachel; Plant, Bernice; Goodwin, Denise; Beck, Ben
Abstract : Background: Injuries are a leading cause of hospitalisation in Western Australia (WA). Injury Matters, a for-purpose injury prevention and recovery organisation, identified the need to assess community attitudes towards unintentional injuries to identify levers for change, establish a baseline measurement and inform resource allocation for creating a safer WA. Methods: A rapid review, an online survey (n=512) and six focus groups (n=26) were completed to; Understand the community's perceptions towards preventing injuries, Understand behavioural influences of injury prevention, and Explore the self-reported incidence of injury prevention behaviours in WA. Tools were developed using previously validated questions, with data collection conducted in 2021/22 with Western Australian adults. Results: Preliminary findings revealed fewer than half of survey respondents expressed concern about the level and frequency of injuries in WA (42%). More than half of respondents believed unintentional injuries were at least slightly preventable (69.7%), with women believing they are less preventable than men. While 70% of respondents believed unintentional injuries were at least slightly preventable, only 34% agreed that 'if I take care of myself, I can avoid injury', suggesting a strong sense of inevitability. Overall, the sample was slightly to moderately willing to take risks. Conclusion: This research provided insight into hazardous injury prevention behaviours and highlighted the need for action to improve Western Australian's injury prevention knowledge. The findings of this project will assist in reinvigorating current initiatives and reimagining future initiatives to instil injury prevention behaviours among the WA community and prevent injuries.